2020
DOI: 10.1177/1468087420909735
|View full text |Cite
|
Sign up to set email alerts
|

Development of an experimental test bench and a psychrometric model for assessing condensation on a low-pressure exhaust gas recirculation cooler

Abstract: A test bench has been designed to assess condensation formation produced on the interior of a low-pressure exhaust gas recirculation cooler working with hot stream of humid air representing an engine warm-up stage, when its coolant starts from very cold conditions. An experimental campaign has been conducted with three different exhaust gas recirculation mass flow rates, four exhaust gas recirculation inlet temperatures and three different coolant initial temperatures, covering common conditions found in the l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 42 publications
0
12
0
Order By: Relevance
“…Ko et al [7] showed that a low ambient temperature highly affected NO x and CO emissions in a Euro 6 diesel engine. Luján et al [8] also discussed this result, who also found a penalty in fuel consumption close to 10% running driving cycles at −7 • C. Despite the interest for the combination of high-pressure (HP) and low-pressure (LP) exhaust gas recirculation (EGR) [9], extremely cold temperatures can also lead to a decrease the EGR rate, as discussed by Galindo et al [10] regarding condensation in the LP-EGR path. In a similar way, operation at high altitude penalizes the engine performance concerning the combustion [11] and gas exchange processes [12], as well as emissions [13].…”
Section: Introductionmentioning
confidence: 88%
“…Ko et al [7] showed that a low ambient temperature highly affected NO x and CO emissions in a Euro 6 diesel engine. Luján et al [8] also discussed this result, who also found a penalty in fuel consumption close to 10% running driving cycles at −7 • C. Despite the interest for the combination of high-pressure (HP) and low-pressure (LP) exhaust gas recirculation (EGR) [9], extremely cold temperatures can also lead to a decrease the EGR rate, as discussed by Galindo et al [10] regarding condensation in the LP-EGR path. In a similar way, operation at high altitude penalizes the engine performance concerning the combustion [11] and gas exchange processes [12], as well as emissions [13].…”
Section: Introductionmentioning
confidence: 88%
“…Cylinder deactivation [7][8][9][10][11] methods are also fairly widely known. However, in addition to a whole number of cylinders, individual cycles [12][13][14][15][16][17] can also be deactivated. This impacts the fuel supply and gas distribution units [18].…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, the use of HP EGR to reduce the NO x levels presents some issues, as per example the appearance of condensation and fouling depositions resulted of a degraded combustion, specially working at low temperatures. 13,14 The soot particles can affect the main components of the EGR line (i.e. EGR valve, EGR cooler, intake manifold) reducing its life span.…”
Section: Introductionmentioning
confidence: 99%